Biologia e potencial de controle de Tetranychus urticae Koch (Acari: Tetranychidae) com fungos entomopatogênicos em mamoeiro - Moro, Larissa Benardino (2009)
Brazil is the worlds largest producer and third exporter of Papaya Carica papaya L., especially the state of Espírito Santo, which accounts for about 70% of exports. Climatic conditions necessary to the development of papaya are also highly favorable for